Electric Delta Trike Stability Characteristic and Maneuverability Analysis: Experiment and Multi-Body Dynamic Simulation - Ignatius Pulung Nurprasetio; Robby Dwianto Widyantara; Bentang Arief Budiman; Rakshidatu Lestaluhu; Djati Wibowo Djamari; Farid Triawan; Muhammad Aziz (Universitas Muhammadiyah Magelang, 2022)
This paper reveals the stability characteristics of an electric-powered delta trike (e-trike), which is developed for goods delivery services. The changeable center of gravity position and weight due to electric component placement and the carried good weight can cause instability of the e-trike. Three main parameters are firstly evaluated on the e-trike: 1) geometry, 2) center of gravity, and 3) stiffness and damping coefficient of the suspensions. Single Lane-Change (SLC) and Double Lane-Change (DLC) tests were then conducted following ISO 14791:2000 and ISO 3888-1:2018 standards, respectively. An e-trike model was created and simulated using SIMPACK, a multi-body dynamic software. The simulation results showed that the developed e-trike model can replicate SLC and DLC tests, indicating the model was valid. A parametric study with the validated model was then conducted with various e-trike weights, center of gravity position, and suspension stiffness and damping ratio values. The results showed additional weight and higher center of gravity position can decrease threshold velocity to avoid rollover. The low suspension stiffness also contributed to lower the threshold velocity. However, the damping coefficient value did not change the threshold velocity significantly. These results can be a guideline in designing a delta trike with better performance in stability and maneuverability.